Evaluation of The Cricket Athlete Coaching Programme - Wahyuningtyas Puspitorini; Widyaningsih, Heni; Chaniago, Herman; Mahyudi, Yafi Velyan (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
Evaluation is part of the supervisory activities of a work carried out by members of the organisation that measures the suitability between the work program and the achievement of work targets. The purpose of this research is to evaluate the coaching of Achievement Sports Club (KOP) athletes involving management and coaches of Cricket. Evaluation is assessed from various aspects, namely Context, Input, Process and Product. The subjects of this research are managers as policy makers, coaches as implementers of activities and athletes as users of programmes and facilities. The survey research method used in this study is by distributing questionnaires to research subjects. The results of this study seen from the Context aspect is the existence of regulations issued by the leadership to provide relief for students who become athletes to continue to get the opportunity to attend lectures, the Input aspect is the determination of the coach, determining the training programme, facilities and infrastructure and recruitment of athletes, the Process aspect is the training implementation mechanism that refers to the suitability of the programme and the Product aspect is showing an increase in their sports abilities, which includes physical, technical and tactical aspects. So that it can be recommended to related parties, namely the development of the FIK UNJ Cricket athlete coaching programme needs to be continuously developed to improve the quality and quantity of the programme.